An 8-Year-Old Child with Malignant Deciduoid Mesothelioma of the Abdomen: Report of a Case and Review of the Literature. (July 2015) - Wolff-Bar, Meirav; Dujovny, Tal; Vlodavsky, Eugene; Postovsky, Sergey; Morgenstern, Sara; Braslavsky, Diana; Nissan, Aviram; Steinberg, Ran; Feinmesser, Meora
Malignant mesothelioma is an uncommon tumor that usually arises in the pleural cavity of adults with a history of asbestos exposure. Less frequently, it appears in the peritoneum or other mesothelial surfaces. Deciduoid mesothelioma is a rare subtype that has been found at both sites. Of the 3 reported cases in children, 2 originated in the mesenterium and 1 in the pleura. We describe a 4th case of pediatric, malignant, deciduoid mesothelioma and a third case in the mesenteric cavity. The patient was an 8-year-old girl who presented with abdominal pain and fullness. Workup revealed extensive involvement of the abdomen by a serosa-based tumor. The clinical and pathologic findings are described, and the pertinent literature is reviewed.